(untitled) (Research, Society and Development, 2021)
Falls play an important role in the degradation of the quality of life of the elderly, and their consequences have a significant impact on the lives of these individuals due to their physical and physiological fragility, generating personal challenges involving emotional aspects and family relationships. Objective: To investigate the nursing performance regarding risk factors and prevention of falls in the elderly population. Methodology: The study is an integrative review with data collection through an electronic search in the National Library of Medicine (Pubmed), Scientifc Electronic Library Online (Scielo), and Latin American and Caribbean Literature on Health Sciences (Lilacs) databases on the topic in question from 2016 to 2021. Results: It was observed that the non-adapted physical space is one of the main risk factors for falling and that it directly implies the economic aspect, other rich factors mentioned were imbalance, stumbling, osteoporosis and medications. We also observed measures that the nursing team can be taking to prevent falls, which were: orientations, dynamics with the family, and home visits. Conclusion: Regarding the analysis of the data present in this review, it is a consensus among the cited authors that nursing plays an essential role in the prevention and care of falls in the elderly, and that it acts directly to mitigate the risk factors.